2022
DOI: 10.3390/cancers14122956
|View full text |Cite
|
Sign up to set email alerts
|

MVI-Mind: A Novel Deep-Learning Strategy Using Computed Tomography (CT)-Based Radiomics for End-to-End High Efficiency Prediction of Microvascular Invasion in Hepatocellular Carcinoma

Abstract: Microvascular invasion (MVI) in hepatocellular carcinoma (HCC) directly affects a patient’s prognosis. The development of preoperative noninvasive diagnostic methods is significant for guiding optimal treatment plans. In this study, we investigated 138 patients with HCC and presented a novel end-to-end deep learning strategy based on computed tomography (CT) radiomics (MVI-Mind), which integrates data preprocessing, automatic segmentation of lesions and other regions, automatic feature extraction, and MVI pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 42 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…Although conventional CT signs such as nonsmooth boundaries, hypohalos, and internal arteries may suggest the presence of MVI, the diagnostic accuracy relies on image quality and expertise of the radiologist. MVI prediction based on deep learning methods is considered a reliable method [10,[28][29][30], and such methods are being increasingly well-established; however, clear interpretable quantitative metrics are still required. Recent studies have shown that quantitative IC plays an important role in tumor diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although conventional CT signs such as nonsmooth boundaries, hypohalos, and internal arteries may suggest the presence of MVI, the diagnostic accuracy relies on image quality and expertise of the radiologist. MVI prediction based on deep learning methods is considered a reliable method [10,[28][29][30], and such methods are being increasingly well-established; however, clear interpretable quantitative metrics are still required. Recent studies have shown that quantitative IC plays an important role in tumor diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of one or two morphological features to establish MVI diagnosis is di cult and inaccurate. Therefore, it is important to improve the diagnostic accuracy by combining quantitative parameters with morphological features [8][9][10]. Radiomics employs high-throughput computation to extract multiple quantitative features from medical images (such as computed tomography [CT] and magnetic resonance imaging [MRI]), which can reveal intratumoral heterogeneity [11].…”
Section: Introductionmentioning
confidence: 99%
“…To automate surgical-procedure-assisted decision making, deep learning-based lesion segmentation models were proposed. In this study, a lightweight transformer architecture called Segformer [ 20 ] was adopted for automatic segmentation of liver tumors, which not only reduced the difficulty of training, but also verified better performance [ 21 ]. The architecture includes a novel hierarchical Transformer encoder and a lightweight all-multilayer perceptron (MLP) decoder.…”
Section: Methodsmentioning
confidence: 99%
“…The results produced by the four models were excellent, with the DL model achieving better results for a few metrics such as AUC (0.906), and sensitivity (93.2%) in the validation set. Wang et al [ 53 ] devised a new DL model named MVI-Mind that consisted of a light-weight transformer for segmentation and a CNN for prediction of microvascular invasion, and several DL techniques were used to compare the proposed methods. The MVI-Mind attained highest mean intersection over union of 0.9006 and accuracy of 99.47% as compared with other DL segmentation algorithms, and it maintained its superiority in prediction and obtained AUC values of 0.9223, 0.8962, and 0.9100 for arterial phase, portal venous phase and delayed period CT images, respectively.…”
Section: Dlrs For Liver Cancermentioning
confidence: 99%